SISTEM INFORMASI AREA PARKIR DI UNIVERSITAS SAHID SURAKARTA - Yosef Chris Bagiyarsa; Sri Huning Anwariningsih; Dwi Retnoningsih (JURNAL GAUNG INFORMATIKA, 2012)
Parking system which is commonly done purposing to put the parking area in order only on giving ticket connected to the computer system in per hour charge. Itmeans the cunsumers have to look for the parking space by them selves. The problem is come up vehicles heapping and overloading coused the unorganized parking area toget a parking space is an unconvenient thing for customers. Building a parking area informative system is a way to overcome this problem Previously the parking system in Sahid University of Surakarta was done manually by area arranging and using a ticket as a user identity for the consequence the users face the difficulty to get a parking space. Based on that fact a computerized informative system is needed to be developed to solve the problem. The system which will be developed is a parking area informative system users a programming language Visual Basic 6.0, My SQL Server as database and seagate crystal report to make a report. It is designed to overcome the unorganized parking area, so it can help the users getting parking area space, and also this computerized sytem will make an addition on security value. By building this new parking area system Sahid University of Surakarta of sha able to overcome the problems such as the vehichles heapping overloading unorganizedparking area and also the difficulty to get a parking space.